Correlation of administrative discretion with the notion and essence of the public administration management activity - Baadzhy, Nataliia A. (My University, 2019)
The article is devoted to the problem of correlation of the notion of administrative discretion with the administrative management activity through understanding the essence of both notions and their interconnection. The problems of the very concept as well as essence of administrative management are raised within the article. It highlights some essential elements of the meaning and nature of administrative discretion along with the grounding its correlation with the administrative management.
Baadzhi N. A. Correlation of administrative discretion with the notion and essence of the public administration management activity / N. A. Baadzhi // Europe an Reforms Bulletin. – 2019. – №. 1 – P. 2-6.
Keywords: administrative discretion; public administration; public administration; activity of public administration; elements of administrative and public activity; state bodies; administrative-legal relations